Physiological Responses of Broiler Chickens to Quantitative Water Restrictions: Haematology and Serum Biochemistry - Iheukwumere, F.C.; Herbert, U. (International Journal of Poultry Science, 2003)
The effect of water restriction on haematology and serum biochemistry of broiler chickens was investigated. A total of ninety six 4-week old Anak broiler birds were used for this study. The birds were divided into 4 treatment groups and within each group, replicated three times at 8 birds per replicate. Different quantities of water were fed to the birds as treatments, that is, ad libitum (To), 3.2 liters (T1), 2.2 liters (T2), 1.2 liters (T3) per day in a completely randomized design (CRD) experiment. The results show that the haematological values were significantly influenced (P